1995
DOI: 10.1001/archsurg.1995.01430010075015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus DNA in Colorectal Adenomas

Abstract: The association of the histological type with HPV-16 and the association of the grade of epithelial dysplasia with HPV DNA were highly significant. These associations support the adenoma-carcinoma hypothesis. In addition, the results suggest that HPV infection may be an important factor for the development of colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Data on the relationship between HPV infection and other factors, including genetic and molecular changes, and the development of CRC from adenomas are not conclusive. Cheng et al (1995) found HPV DNA in 28% of 109 paraffin-embedded adenomas. In contrast, Burnett-Hartman et al (2013) did not find HPV DNA in an assessment of 167 colorectal adenomas, 87 hyperplasic polyps, and 250 polyp-free controls.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the relationship between HPV infection and other factors, including genetic and molecular changes, and the development of CRC from adenomas are not conclusive. Cheng et al (1995) found HPV DNA in 28% of 109 paraffin-embedded adenomas. In contrast, Burnett-Hartman et al (2013) did not find HPV DNA in an assessment of 167 colorectal adenomas, 87 hyperplasic polyps, and 250 polyp-free controls.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies of colorectal adenomas, HPV DNA detection varied, ranging from 0–38% (11, 12, 22), and one of these studies reported a statistically significant difference in the proportion of adenomas positive for HPV DNA (38%) compared to normal colonic tissue from disease-free controls (8%) (12). However, PCR, and particularly nested PCR, is prone to contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation in the control specimen, all studies confirmed an association between HPV detection rates, specifically subtypes 16 and 18, and CRC with odd ratio ranging between 2.7 (95% CI, 1.1-6.2) and 9.1 (95% CI, 3.7-22.3). (Cheng et al, 1995;Kirgan et al, 1990). Moreover, the strength of association was related to the degree of tumour dysplasia.…”
Section: Cancer In Humanmentioning
confidence: 95%